Creating the Future of Work - Hallin, Anette (Edward Elgar Publishing, 2025)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This timely book explores the ways in which the future of work and associated digital technologies are imagined in contemporary society. Drawing on a wealth of original research, the book features detailed case studies that link broad sociological concepts to everyday practice.